Changes in the Relative Importance of the Minimum Wage, Income Support and Employment Support Programs - Heesuk Yun (Korea Development Institute (KDI), 2016)
Because there is a significant mismatch between low wage and low income, policies tackling the poverty issue must focus on low income households rather than low-wage workers and emphasize the EITC or labor market policies that support low income households rather than the role of the minimum wage system that supports low-wage workers. - Household income is determined by the number of employed members, wage, market income other than earned income, and government transfers. The presence of an employed member is critical to the conditions of falling into poverty. - Only 21.7% of low-wage workers are poor. - 30.5% of the below-minimum wage workers are poor, and 69% of the below-minimum non-poor workers were found to live above the poverty line due to other household members' earned income. - In order for a four-member household with a single minimum-wage worker not to fall into poverty, the wage needs to be raised by 53.6% while the addition of an extra income earner working three hours a day could help them stave off poverty if the EITC coverage expands slightly. - Unemployed members in the low income class are mostly seniors and the less educated. The higher income the household has, the lower the age of its unemployed member and higher its education level is. - Among the able-bodied poor, only 9.4% participated in employment support programs, while 68.2% benefited from income support. - Concrete targets are important when designing a combination for the minimum wage program and EITC for income security, for example 'to secure the income of households with 1.5 income earners with two children to help them stay above the poverty line.' - Anti-poverty policy for households with the ability to work should focus on enhancing their economic activities.
Keywords: 330